2008
DOI: 10.1017/s1352465808004864
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to CBT: Stepped Care and CBT Self-Help Models in Practice

Abstract: The delivery of cognitive behaviour therapy (CBT) in the UK has moved through two phases. In the first phase specialist practitioners delivered bespoke CBT to individuals often experiencing complex and longer-lasting problems. This phase has been characterized by waiting lists and a high quality service delivered to a few. In the second phase of service delivery CBT has begun to be delivered in all sorts of different formats, including CBT selfhelp/guided CBT, behavioural activation, computerized CBT and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…In this work we drew on a structured CBT approach 25,26 , which has been established as effective 27 . It has been successfully adapted for use by CHWs to address mental health concerns in perinatal populations in rural Pakistan 23,24 , showing the effective use of CHWs to deliver such interventions in a Muslim population 23,28 . Task shifting to using CHWs to deliver interventions primarily delivered by behaviorists can be seen as an important aspect of delivering more accessible, efficient, cost-effective services 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work we drew on a structured CBT approach 25,26 , which has been established as effective 27 . It has been successfully adapted for use by CHWs to address mental health concerns in perinatal populations in rural Pakistan 23,24 , showing the effective use of CHWs to deliver such interventions in a Muslim population 23,28 . Task shifting to using CHWs to deliver interventions primarily delivered by behaviorists can be seen as an important aspect of delivering more accessible, efficient, cost-effective services 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several barriers to patient access to CBT and other evidence-based practice (EBP), but one of the main factors is the lack of professionals trained in their use (Cartreine, Ahern, & Locke, 2010;Olfson et al, 2009;Weissman et al, 2006;Weisz, Hawley, & Jensen-Doss, 2004;Williams & Martinez, 2008). Consistent with the advances made in mental health treatment and the ongoing calls from key organizations (e.g., National Institute of Mental Health; Association for Behavioral and Cognitive Therapies [ABCT]) to "[promote] the utilization, expansion, and dissemination of behavioral, cognitive, and other empirically-derived practices" (ABCT, 2008), more and more resources are being allocated to dissemination and implementation efforts.…”
mentioning
confidence: 99%
“…However, these authors noted that cognitive restructuring techniques may be problematic within ARBD rehabilitation, due to impaired memory and issues with abstract thought. It is therefore suggested that low intensity behavioural strategies, such as behavioural activation may be more beneficial in the psychosocial rehabilitation of ARBD (Williams & Martinez, 2008).…”
Section: Discussionmentioning
confidence: 99%